1993
DOI: 10.1111/j.1365-2796.1993.tb00728.x
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of clinical diagnoses in a teaching hospital: a review of 997 autopsies

Abstract: If autopsies are heeded without bias, they will continue to give important feedback concerning medical diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
1
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 18 publications
2
23
1
1
Order By: Relevance
“…In 50% of cases, the diagnoses were made at autopsy, and many times they included important diseases such as bronchopneumonias (46%), neoplasias (37.9%), venous thromboses (82.5%) and pulmonary embolisms (80.3%). These data agree with the literature, which shows that 45% of the bronchopneumonias are diagnosed at autopsy (6), as well as 26 to 44% of the neoplasias (6,21,23,24) and 87% of the pulmonary embolisms (15,25).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In 50% of cases, the diagnoses were made at autopsy, and many times they included important diseases such as bronchopneumonias (46%), neoplasias (37.9%), venous thromboses (82.5%) and pulmonary embolisms (80.3%). These data agree with the literature, which shows that 45% of the bronchopneumonias are diagnosed at autopsy (6), as well as 26 to 44% of the neoplasias (6,21,23,24) and 87% of the pulmonary embolisms (15,25).…”
Section: Discussionsupporting
confidence: 82%
“…Class I discrepancies are found in 7 to 13% of cases, and class II in 15 to 25% (7,9,(11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Cardiovascular diseases were found to be the main cause of death (42.8%) of autopsy diagnoses, confirming the impact of cardiovascular findings described by other authors 6,10,13 . The 8% autopsy rate in our series is similar to hospital autopsy rates in the United States (12%) and some studies in United Kingdom (11 to 24%) 14 .…”
Section: Discussionsupporting
confidence: 76%
“…Discrepancies between clinical and pathology diagnoses may occur due to the high frequency of the disease, diagnostic difficulties, or even because of the sudden nature of some diseases (myocardial infarction, aorta dissection, pulmonary embolism, stroke), which do not allow adequate time for clinical investigations 10 .…”
mentioning
confidence: 99%
“…In the United States, autopsy rates of death due to overall causes and stroke have been progressively declining since 1972, and less than 5% of deaths attributed to stroke have been documented by autopsy since 1982 [8] . However, studies addressing the accuracy of clinical diagnoses using autopsy as the gold standard have revealed that postmortem examination is still a useful tool for diagnosis mainly among the elderly [9,10] . An intensivecare-based study revealed that 66.7% of the clinical diagnoses of the basic cause were correct, and that in 23.3% of cases, an error in the diagnosis of the basic cause occurred which, if detected before death, would probably have changed the patient's treatment and clinical course [11] .…”
Section: Discussionmentioning
confidence: 99%